Epidemiology of hepatitis B infection among the Nicobarese – a mongoloid tribe of the Andaman and Nicobar Islands, India - MURHEKAR, M. V.; MURHEKAR, K. M.; ARANKALLE, V. A.; SEHGAL, S. C. (Epidemiology and infection, 2002)
Andaman and Nicobar Islands, Union Territory of India, is home to six primitive tribes. Preliminary serological studies carried out earlier among the four accessible tribes revealed that hepatitis B virus (HBV) infection is hyper-endemic among them. The present study was carried out to understand important modes of transmission and to identify possible risk factors associated with HBV infection among the Nicobarese tribe. The epidemiology of HBV infection in these islands appears to be distinct with a high prevalence of the chronic carrier state (22·2%) associated with a comparable proportion of the population being anti-HBs positive (26·3%). More than half of the HBsAg and anti-HBs negative individuals have anti-HBc antibodies. Age, past history of hospital admission, intramuscular injections and number of carriers in the tuhet were found to be significantly associated with exposure to hepatitis B virus. Horizontal transmission through close contact with carriers and perinatal route appears to be an important mode of transmission of HBV in this community. Besides this, use of unsafe injections represents an independent risk factor for acquiring HBV infection in this population. Introducing HBV vaccine in the infant immunization programme and improving injection safety would help to control the infection in the tribal community of these islands.